The effect Analysis of Grammar Mastery towards Writing English Skill - Jimmi Daniel (Wanastra: Jurnal Bahasa dan Sastra, 2017)
The objective of this research is to know the correlation between grammar mastery and writing English skill of student Grade X SMK Selagan Jaya Jakarta. The population is taken from SMK Selagan Jaya Jakarta. The sample of research is twenty students. The method used correlative descriptive by sampling randomly technique which is writing test. The data is taken from grammar mastery 56 as lowest score, 96 as highest score; X = 73,3 and S = 15, 46. For writing English skill the lowest score is 52, the highest 92; X= 67, 6, and S = 13, 65. The next step is to know the effect of grammar mastery towards writing English skill, the writer uses correlation product moment by finding rxy = 0, 9889 on table significant 0,05 bigger than F table shown0, 444. This criteria’s shows the correlation was high. So, this research have been succeed to reject of zero hypothesis which is said no effect between grammar mastery towards writing English skill of student grade X SMK Selagan Jaya Jakarta. This result of the result been done can be useful for English teacher to increase their competence of grammar mastery and provide an appropriate task for students